FINNED CHANNEL OPTIMIZING IN RADIO ELECTRONIC DEVICES FOR FORCED AIR COOLING SYSTEMS - Krischuk, V. N.; Shilo, G. N.; Kaspyrovych, N. A.; Ogrenich, E. V. (Radio Electronics, Computer Science, Control, 2014)
The finned channel is used as a simplified model for the analysis of thermal conditions of cartridge design electronic equipment with a high power density for forced air cooling. The finned channel thermal model and method of its creating are described by the computeraided engineering systems. Clearance limitations of the radio electronic units and the manufacturing limitations on width of fins and their numbers are considered during creating the thermal model. The finned channel thermal characteristics that include the thermal resistance dependence on parameters of fins (width, length, number) are investigated. The approximating functions for these dependencies are proposed. To minimize the thermal resistance the correlations for finned channel having the optimal sizes are obtained. The iteration optimization algorithm is developed. This approach provides high accuracy. In the algorithm the thermal conditions are calculated by the computeraided engineering systems. The example of designing the finned channel with optimal thermal conditions is showed. As a result of optimizing the finned channel thermal resistance decreased by 35 %.